Impacto da reabilitação pulmonar nos marcadores inflamatórios pré-operatórios e nas complicações pulmonares pós-operatórias de pacientes com câncer de pulmão candidatos a ressecção pulmonar - Morano, Maria Tereza Aguiar Pessoa (2011)
Lung cancer (LC) is a malignant aggression which can be also surgically treated characterized by inflammation and higher mortality rates. Pulmonary complications are still concerning. The choice of studying fibrinogen and albumin is due to the fact that they are active inflammatory markers in LC often associated with chronic obstructive pulmonary disease. Pulmonary complications subsequent to lung resection are still worrying. This study evaluated the impact of Pulmonary Rehabilitation (PR) on preoperative inflammatory markers and postoperative pulmonary complications of LC patients. Controlled clinical trial with 31 patients with moderate to severe obstructive disease, stages IA to IIIA, randomized into Group A (GA) undergone PR and the control group - Group B (GB) undergone respiratory therapy (RT). Pulmonary function, respiratory muscle strength, functional capacity, upper limbs muscle strength, maximum and submaximal exercise capacity, Hospital anxiety and depression scale (HADS), quality of life through Short-form36 (SF36), fibrinogen and albumin were evaluated before and after a 4 weeks of the survey protocols. After surgery pulmonary complications were analyzed. GA performed aerobic physical training, peripheral and respiratory muscle strength training. GB performed lung expansion techniques. Both groups received educational classes and performed the protocols in similar time. The study was approved by the institution’s ethic committee. There was in GA significant improvements in FVC from 65±17 to 76± 15% of its predicted (p=0.003 ), in maximal inspiratory pressure (MIP) from 78±46 to 104± 42cmH2O (p=0.0003 ), in maximal expiratory pressure (MEP) from 78±21 to 93± 25cmH2O (p=0.0009 ); in walked distance from 435±70 to 491±88 m (p<0.0001 ), upper limb maximum load from 1.0 to 2.0 kg (p=0.008 ), in treadmill inclination from 5±3 to 8± 3% (p<0.0001 ) and speed from 4.9 [3.7 -5.5] to 5.2 [4.4 -6] (p=0.002 ), submaximal exercise capacity from 447±179 to 718± 220s (p=0.002 ), in anxiety from 9.9 ±4.9 to 4.9 ±2.7 (p<0.0001 ), and depression from 9.05 ±4.08 to 4.9 ±2.1 (p<0.0001 ), in quality of life with Physical Component Summary (PCS) from 37.5 ±9.07 to 46.15 ± 8.7 % (p=0.004 ) and fibrinogen to 448.3 ±129.9 to 321.6 ± 73.2 mg/dl (p=0.0002 ). Albumin has not showed significant result in both groups. In GB there was significant increase in MIP 50±22 to 70± 35 (p=0.004) and reduction in fibrinogen from 490.7 ± 199.7 to 453.3 ± 177.2 mg/dl (p=0.3). Other variables GB did not show any significant results. When comparing results between groups there was significant difference in the walked distance (p=0,0001), in upper limb strength (p=0,009), in inclination (p=0,0008), in endurance (p=0,005), in anxiety (p=0,0002), in depression (p=0,04), in PCS (p=0,03) and fibrinogen (p=0,04). Out of 31 patients, 10 were not operated. In postoperative pulmonary complications, GA show less greater and lesser relevance morbidity (p=0,002 and p=0,01 respectively) shorter length of hospital stay (p=0,004), less chest tube days(p=0,03), lower percentage of bronchial fistula (p=0,009) and less bronchospasm (p=0,002). When compared to GB. PR had impact on the reduction of serum fibrinogen, on clinical improvements, health related quality of life, anxiety and depression, and also reduced postoperative pulmonary complications. In the absence of PR programs, RT can be an important preoperative strategy.